Consumidor com deficiência: implicações de fatores pessoais e contextuais no consumo em redes varejistas de João Pessoa-PB - Mano, Rayane Fernandes (2014)
The objective of study is to undersand the relations between personal, structural and sociocultural factors and the consumption behavior of people with physical and visual disabilities in supermarkets of João Pessoa-PB. In this way, theories were approached regarding the Transformative Consumer Research, Multiculturalism, Identities, Minority Groups , Historical Models of people with disabilities, Disabled Consumer and Retail in the context of disability. At first, it was designed three dimensions of disabled consumption with disabilities, that was Environmental, socialcultural and personal factors. The adopted methodology was oriented by the transformative paradigm, applying three distinct stages in the empirical research, corresponding to (1) architectural mapping of the most popular supermarkets of the city, (2) interviews with consumers with physical and visual disabilities and (3) naturalistic observation of a consumption process of a disability consumer. The strategy used in the data collection was, at first, a list of parameters based on ABNT 9050, in order to measure the adequacy levels of accessibility in retail environment. So, it was mensured the accessibility level of 04 supermarkets and 04 hypermarkets of João Pessoa. In the second phase of this research, it was conducted 16 in-depth, semi-structured and face-to-face interviews, that was based and structured on the three dimensions previously outlined. Finally, in stage of the naturalistic observation, it was used personal notes to write the facts and impressions that was capture during the consumption process of a wheelchair consumer in an hipermermarket of João Pessoa. The fulfilment of these three research stages provided an overview of the consumption of these people in the local retail supermarkets and hipermarkets. Over and above the physical/structural inaccessibility found in these stablishments, it is often found a lot ofsocial and cultural barriers, represented by inadequate forms of treating and wrong conceptions about them,. However, it doesn‟t prevent these consumer from going to stores, picking their products, checking prices,chosing brands, or having a positive outlook of themselves as people and consumer. For them, the time to go shopping in the supermarkets means pleasure, autonomy, self-affirmation and freedom